2019
DOI: 10.1111/jce.14271
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of acute procedural outcomes within four generations of cryoballoon catheters utilized in the real‐world multicenter experience of 1STOP

Abstract: Introduction Four generations of the cryoballoon (CB) catheter were retrospectively evaluated in a real‐world examination of patients with atrial fibrillation (AF). Methods and Results Four hundred eighty patients (27% female and 60 ± 10 years) suffering from AF, underwent pulmonary vein (PV) ablation with one‐of‐four generations of the CB catheter. The total cohort was divided into four groups of patients: 120 with first‐generation (CB‐1); 120 with second‐generation (CB‐2); 120 with third‐generation (CB‐3); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…A real‐world study evaluating 480 patients, 120 in each generation group, found a progressive reduction in procedural duration (150 min, 95 min, 90 min, and 75 min, from CB‐1 to CB‐4, as well as a reduction in fluoroscopy time and ablation duration, with the same success rate. This denotes that even if reaching a higher success was not possible, the evolution in balloon architecture improved the handling, making the procedure easier 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A real‐world study evaluating 480 patients, 120 in each generation group, found a progressive reduction in procedural duration (150 min, 95 min, 90 min, and 75 min, from CB‐1 to CB‐4, as well as a reduction in fluoroscopy time and ablation duration, with the same success rate. This denotes that even if reaching a higher success was not possible, the evolution in balloon architecture improved the handling, making the procedure easier 11 …”
Section: Discussionmentioning
confidence: 99%
“…The Arctic Front Advance ST™ (CB‐3; Medtronic) had a shorter distal nose‐tip on the balloon, which facilitated the real‐timed assessment of pulmonary vein potentials 10 . Currently, most AF cryoablations are performed using the Arctic Front Advance PRO™ system (Medtronic), the 4th generation device, characterized by better catheter maneuverability and ergonomics, achieving shorter procedural times 11 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, an interesting study evaluated four generations of CBG in the treatment of AF. The CBG4 application showed a higher rate of TTI visualization, faster procedural ablation times, and a lower rate of acute complications in comparison to the previous generations [22], while the long-term outcomes associated with CBG4 are still unclear.…”
Section: Development Of the Cryoballoon Catheter Is Helpfulmentioning
confidence: 93%
“…PV isolation with cryoballoon ablation has gained wide acceptance due to its high rate of success and simplicity of the technique. When successful, a single application of ≤240 s can be applied to isolate a vein, and single-shot procedures (1 application for all veins) are common (25-45%) [19,20]. Currently, there are two manufacturers (Medtronic Inc., Minneapolis,…”
Section: Cryothermal Ablationmentioning
confidence: 99%